Issues of judicial supervision of the exercise of the discretionary power by administrative authorities - Markosyan, Tigran; Ghimoyan, Satik (Bulletin of Yerevan University C: Jurisprudence, 2021)
Within the framework of the judicial supervision criteria for assessing the legality of the exercise of discretionary powers, the peculiarities presented by the court on the position of illegal exercise of discretionary powers by the administrative agencies, there are several problems due to uncertainties at the legislative and practical levels. In this article, based on the theoretical sources, foreign and domestic legislation and case law are analyzed the present issues of judicial control over the lawful exercise of discretionary powers. As a result of the study, authors have introduced a number of scientific-practical conclusions, including analyses in the context of the principle of separation of powers and ne bis in idem principle.